Perhitungan Jumlah Bahan Bakar LPG, Minyak Tanah, Kayu Bakar, Bensin Dan Solar Di Kecamatan Siak Hulu Dan Kecamatan Tambang Kabupaten Kampar - Suci Hartina Fani Putri; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Siak Hulu Subdistrict and Tambang Subdistrict are sub-districts in Kampar District which are supporting areas of Pekanbaru City because many people work and attend schools in Pekanbaru City but live in Siak Hulu Sub-District and Tambang District. The high number of residents with a variety of activities will certainly influence the amount of CO2 emissions produced. Primary data was obtained from the survey involving 298 respondents and secondary data, regional maps amddemographic data. The variables in this research are the amount of LPG fuel, kerosene, and fuel wood and BBM (fuel oil) for generator engines, namely gasoline and diesel. Calculation of CO2 emissions was carried out using the IPCC method (2006). Total primary CO2 emission from household activities in Siak Hulu Subdistrict and Tambang District are 1346,802 tons CO2/month.Keywords: Carbon Footprint, Household CO2 Emissions, Fossil Fuels